Introducing integrated rice-fish farming in Lao PDR: policy engagements - Inphonephong, Souphalack; Mam, K.; Phounvisouk, L.; Dubois, Mark (International Water Management Institute, 2024)
This report outlines policies and recommended policy engagements to promote agroecology practices in food production systems in the Lao People’s Democratic Republic (Lao PDR). Literature reviews and field consultation visits were used to collect data on factors and challenges influencing the integrated rice-fish farming practices by farmer households and policy engagements to enhance their local potential and address challenges that may prevent further expansion and sustainable practices.